Fertility in relation to time of insemination in Assam local goat - BHATTACHARYYA, H K; GOSWAMI, B K; BARUA, P M; CHAKRAVARTY, P; BISWAS, R K (The Indian Journal of Animal Reproduction, 2023)
One hundred and eleven adult female healthy Assam Local Goats belonging to organisedfarm and private breeders were used to determine the best time of insemination for conception. Oestruswas detected either by a vasectomised buck or manual observation. Goats were inseminated with frozensemen of a proven buck. Assumption of conception by non-return basis was confirmed by actual kidding.The highest conception rate was recorded in goats inseminated at 36 hours, followed by 42, 30 and 24hours of onset of oestrus. The overall conception rate was higher in goats at organised farm as comparedto those with private breeder.
Keywords: Frozen semen; Al; fertility; oestrus; goat